The effects of a maternal personality, children’s behavioral characteristics, and parenting styles on the dental anxiety of 3- to 6-year-old children - Ibis, Sevgin; Sari, Mustafa Erhan; Tomak, Lemak; Babadagi, Zehra; Karabekiroglu, Koray Mehmet Zeynel (UI Scholars Hub, 2019)
Background: Many individual and environmental factors cause dental anxiety in children. The aim of this study was to examine the effects of a maternal personality, children’s behavioral characteristics, and parenting styles on the dental anxiety of three- to six-year-old children. Methods: The parents of 230 children who applied to the Department of Pediatric Dentistry, Faculty of Ondokuz, Mayıs University were involved in this study. The “Temperament and Character Inventory”, “Child Behavior List”, and “Parenting Attitude Scale” were applied to the volunteer parents. All data were statistically analyzed (p < 0.05). Results: From the results of determining the maternal personality, it was found that the score of “novelty seeking” and those of all the character dimensions were statistically significantly higher in the dental anxiety group than in the control group, while the scores of “reward dependence” and persistence were statistically significantly lower in the dental anxiety group (p < 0.001). From the aspect of children’s behavior characteristics, the scores of “inhibitory control” (p = 0.029) and permissive attitude among the parenting styles were statistically significantly higher in the dental anxiety group (p = 0.027). Conclusion: In this study, it was determined that maternal characteristics, children’s behavioral characteristics, and parenting attitudes affect the dental anxiety of three- to six-year-old children.